2020
DOI: 10.1097/adm.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclical and Evolving Nature of Methamphetamine Use: An Evaluation of Near Real-time Urine Drug Test Results

Abstract: Objective: To determine methamphetamine positivity and copositivity with other drugs in urine drug test (UDT) results geographically through time. Methods: This cross-sectional study of UDT results from January 1, 2014, through December 31, 2019, included patient specimens submitted by health care professionals across the United States. The analysis used LC-MS/MS to detect cocaine, heroin, alcohol, marijuana and nonprescribed methamphetamine, fentanyl, methadone, bupren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…UDT has been used to examine trends in substance use (not specific to patients treated for OUD). 6,[13][14][15] Furthermore, prior studies have examined UDT findings among OUD patients treated at single sites or hospital health systems. 9,16,17 We are not aware of any studies that specifically examine national trends in definitive UDT findings among OUD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UDT has been used to examine trends in substance use (not specific to patients treated for OUD). 6,[13][14][15] Furthermore, prior studies have examined UDT findings among OUD patients treated at single sites or hospital health systems. 9,16,17 We are not aware of any studies that specifically examine national trends in definitive UDT findings among OUD patients.…”
Section: Introductionmentioning
confidence: 99%
“…UDT can provide an important window into the changing substance use issues among patients treated with medications for OUD. UDT has been used to examine trends in substance use (not specific to patients treated for OUD) . Furthermore, prior studies have examined UDT findings among OUD patients treated at single sites or hospital health systems .…”
Section: Introductionmentioning
confidence: 99%
“…This study also compared the turnaround time of the two testing methods and found that the urine sediment occult blood test had a longer turnaround time than urinalysis. The more efficient urinalysis is recommended for emergency cases to avoid delaying the diagnosis and treatment [13,14] .…”
Section: Discussionmentioning
confidence: 99%